2016
DOI: 10.1007/s11664-016-4810-0
|View full text |Cite
|
Sign up to set email alerts
|

Half-Heusler Alloys for Efficient Thermoelectric Power Conversion

Abstract: Half-Heusler (HH) phases (space group F43m, Cl b ) are increasingly gaining attention as promising thermoelectric materials in view of their thermal stability and environmental benignity as well as efficient power output. Until recently, the verifiable dimensionless figure of merit (ZT) of HH phases has remained moderate near 1, which limits the power conversion efficiency of these materials. We report herein ZT~1.3 in n-type (Hf,Zr)NiSn alloys near 850 K developed through elemental substitution and simultaneo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The Lorenz numbers used in the calculation were obtained from the Seebeck coefficient based on the empirical equation proposed by H. S. Kim etc. 33 34 .…”
Section: (A)mentioning
confidence: 99%
“…The Lorenz numbers used in the calculation were obtained from the Seebeck coefficient based on the empirical equation proposed by H. S. Kim etc. 33 34 .…”
Section: (A)mentioning
confidence: 99%
“…Sb is found to be an effective dopant for n-type ZrNiSn half-Heusler alloys which effectively increases the carrier concentration and also reduces thermal conductivity [36]. Chen et al reported high zT of 1.3 in n-typeHf 0.65 Zr 0.25 Ti 0.15 NiSn 0.995 Sb 0.005 /nano-ZrO 2 composition at 850 K [195]. Such high zT resulted from Figure 15.…”
Section: Half-heusler Alloysmentioning
confidence: 98%
“…Due to Ti substitution, phonon scattering is enhanced which reduces lattice thermal conductivity. On the other hand, ZrO 2 nanoparticles act as potential barriers for carrier scattering that enhances the thermopower [195]. Among the prospective half-Heusler alloys are also p-type FeNbSb and α-MgAgSb based materials [196,197].…”
Section: Half-heusler Alloysmentioning
confidence: 99%
“…The results show that thermoelectric MPEA have high ZT comparable to that of state-of-the-art materials. The high-ZT MPEA (filled symbols) shown in Figure 4 include: Bi0.5Sb1.5Te2.7Se0.3, 1.12, 303 (Xu et al, 2012), where the first number is ZT and second number is the temperature at which ZTmax occurs; (GeTe)80(AgSbTe2)20, 1.75, 773 ; (PbTe)0.84(PbSe)0.07(PbS)0.07Na0.02, 2, 800 (Korkosz et al, 2014); Pb0.92Mg0.08Te0.8Se0.2Na0.02, 2.2, 820 (Fu, 2016); Cu0.8Ag0.2In0.5Ga0.5Te2, 1.6, 900 ; Cu1.95Ag0.05S1/3Se1/3Te1/3, 1.9, 1000 ; Ti0.5Zr0.25Hf0.25NiSn, 1.5 820 (Rogl et al, 2018); Hf0.65Zr0.25Ti0.15NiSn0.995Sb0.005, 1.3, 830 (Chen et al, 2016); ZrCoBi0.65Sb0.15Sn0.20, 1.4 970 ; Ta0.74V0.1Ti0.16FeSb. 1.52, 973 (Zhu et al, 2019).…”
Section: State-of-the-art Thermoelectric Mpeamentioning
confidence: 99%
“…Each symbol may represent several alloys with the same ZT. Mass and strain fluctuations from Hf/Zr/Ti and nanostructure enhance phonon scattering (Chen, 2016) Ti0.5Zr0.25Hf0.25NiSn0.98Sb0.02 n-type 1.2 Phase separation and mass and strain fluctuations (Gürth, 2016) Ti0.5Zr0.25Hf0.25NiSn n-type 1.5 Phase separation and mass and strain fluctuations (Rogl, 2018) FeNb0.86Hf0.14Sb single dopant p-type 1.5…”
Section: (A) Half-heusler Compoundsmentioning
confidence: 99%